Overview of national plan for NHS blood and transplant and hospitals to address blood shortage in the United Kingdom (Series 2): Comprehensive summary of blood emergency management and United Kingdom National Blood Transfusion Committee (NBTC) - GUO Jin; GUO Yongjian; WANG Hongjie; WANG Yong (Zhongguo shuxue zazhi, 2025)
As the second installment in our series introducing the UK Blood Shortage Response Plan, this article outlines the UK's blood emergency management framework, including: Business Continuity Management (BCM) for healthcare institutions; Structure of emergency command coordination and participating organizations in the UK; Key components of blood emergency management guidelines. Simultaneously, by detailing the National Blood Transfusion Committee's component agencies, institutional responsibilities, operational requirements and operational remit, it provides deeper insights into the development and functioning of the UK's blood emergency management system, thereby delivering comprehensive foundational knowledge for understanding the implementation of the Blood Shortage Response Plan.